Chloride penetration in concrete exposed to cyclic drying-wetting and carbonation. (1st June 2016) - Ye, Hailong; Jin, Xianyu; Fu, Chuanqing; Jin, Nanguo; Xu, Yibin; Huang, Tao
Highlights: Concrete performance exposed to a combination of various deterioration mechanisms. Chloride penetration in concrete under cyclic drying-wetting and carbonation. Effects of supplemental cementitious materials and flexural loading are presented. Coupled physical-chemical interaction between environments and concrete materials. Abstract: In this paper, the chloride penetration process in concrete exposed to a cyclic drying-wetting and carbonation environment was experimentally characterized. In order to better represent the concrete in service, chloride penetration tests were performed on concrete with various levels of flexural loading and incorporation of supplemental cementitious materials (i.e. blast-furnace slag and low calcium fly ash). The result shows that the chloride penetration profile in concrete is a result of multiple interactive deteriorating mechanisms and dependent on the properties and stress status of concrete itself. Carbonation induces considerable chloride (both free and bound) redistribution in concrete, rendering chloride ions ingress from carbonated region towards un-carbonated region. The incorporation of supplemental cementitious materials makes concrete more vulnerable to carbonation-induced chloride movements due to its less amount of portlandite. The increased magnitude of flexural loading results in higher chloride content in concrete probably by forming some micro-cracks.